Праця О. О. Русова в Київському комерційному інституті - Чуткий, А. (Сiверянський лiтопис, 2015)
У статті досліджено роботу О. О. Русова у Київському комерційному інституті. Встановлено, що його перехід на роботу до цього ВНЗ був особистим бажанням.
З’ясовуються усі складові діяльності О. О. Русова у Київському комерційному інституті: викладацька діяльність (зокрема й організація цікавих дослідницьких проектів за
участю студентів), робота в складі управлінських органів інституту, редакторство
«Відомостей Київського комерційного інституту», організація низки наукових товариств при інституті. Все це засвідчує щире зацікавлення О. О. Русова своєю роботою у цьому навчальному закладі і водночас – особливу увагу до молоді та прагнення прищепити їй любов як до наукової діяльності, так і український патріотизм. В статье исследуется работа А. А. Русова в Киевском коммерческом институте.
Установлено, что его переход на работу в этот вуз было личным желанием Русова.
Выявлены все составляющие деятельности А. А. Русова в Киевском коммерческом
институте: преподавательская деятельность (в частности организация интересных
исследовательских проектов с участием студентов), робота в составе управленческих
структур института, редактирование «Известий Киевского коммерческого института», организация ряда научных обществ при институте. Все это свидетельствует о искренней заинтересованности А. А. Русова своей работой в этом учебном заведении и одновременно – особое внимание к молодежи и стремление привить ей любовь как к научной деятельности, так и украинский патриотизм. The article examines the main component of professional A. A. Rusov’s activity in 1909–
1915 in the Kyiv Commercial Institute. It is established that his transfer to this University
was the personal Rusov’s desire and the case was instituted in 1908, but was held in 1909.
Turns out all components of the A. A. Rusov’s work in Kyiv Commercial Institute. These
were – teaching activities (including organization of interesting research projects involving
students), work in the composition of the governing bodies of the Institute Training Committee
and the Council of the Kyiv Commercial Institute; the editorship of the «News of the Kyiv
Commercial Institute», organization of several scientific societies at the Institute. All this
shows A. Rusov a sincere interest their work at this institution and at the same time, special
attention to young people and the desire to instill in her a love for science and Ukrainian patriotism. The latter is evidenced in particular by the fact that among the students who wrote the scientific work under the guidance of A. A. Rusov were subsequently active participants in the Ukrainian liberation movement in 1917–1921. It is established that the discharge was initiated and invitations to teach at the Kyiv Commercial Institute is also the wife of A. A. Rusov – Sofia, which was supported by the leadership of this University. However, this was rejected by the Ministry of trade and industry of the Russian Empire, which was one manifestation of the continued repressive policies against prominent figures of the Ukrainian national movement from the Imperial power. Similarly, the Ministry had rejected the proposal of the leadership of the Institute on the appointment of Rusov’s extraordinary Professor.